Penerapan Model Pembelajaran Kooperatif Tipe Think Pair Share (TPS) untuk Meningkatkan Hasil Belajar IPAS Kelas - Permata, Dinda; Dary, Pasha Wulan; Sevia, Diina Septi; Wulandari, Noni; Frima, Aren (JOEAI (Journal of Education and Instruction), 2026)
This study aims to improve the science and social studies (IPAS) learning outcomes of fourth-grade elementary students through the implementation of the Think Pair Share (TPS) cooperative learning model. This research is a Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research subjects were 18 fourth-grade students of SD Negeri 32 Lubuklinggau. Data were collected through tests, observation, and documentation. The results showed a significant improvement in student learning outcomes. In Cycle I, the average pretest score was 52.2 with 28% mastery, which increased to 66.7 with 67% mastery in the posttest. In Cycle II, the average pretest score was 66.1 with 39% mastery, and increased to 80.6 with 89% mastery in the posttest. Thus, the Think Pair Share learning model is proven to be effective in improving students’ learning outcomes in IPAS.   Keywords: Think Pair Share, Learning Outcomes, IPAS, Cooperative Learning